Lemmus portenkoi Tchernyavsky 1967 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Lemmus portenkoi Tchernyavsky 1967 Lemmus portenkoi Tchernyavsky 1967, Zool. Zh., 46: 12. Type Locality: Russia, SE Siberia Magadanskaya Oblast, Ostrov Vrangelya (Wrangel Isl). Vernacular Names: Wrangel Island Lemming. Distribution: Endemic to Wrangel Isl. Discussion: Jarrell and Fredga (1993) included portenkoi in L. sibiricus , observing their convention of synonymizing insular taxa with mainland species. However, Chernyavskii et al. (1993) interpreted the cytogenetic and morphological peculiarities of the Wrangel Isl form to reflect an old Palearctic origin and regarded it as a separate species. Although Wrangel Isl lies close to the Chukotskiy mainland, where L. trimucronatus occurs, cytochrome b sequence data instead link the island populations with those farther west that we recognize as L. amurensis (Fedorov et al., 1999 b ); the percent sequence divergence between the Wrangel Isl lemming and L. amurensis approximates that distinguishing L. lemmus and L. sibiricus , which together with the information provided by Chernyavskii et al. (1993), lends support to its recognition as a species. Wrangel Isl provides habitat for another endemic lemming, Dicrostonyx vinogradovi (see that account), yet that species is more closely related to Nearctic, not Eurasian, forms according to mitochondrial DNA haplotypes (Federov, 1999; Fedorov et al., 1999 a ). During the Pleistocene, the island merged with the Beringian land mass, including the mainland east of the Kolyma River stretching into Alaska; Fedorov et al. (1999 b ) developed historical arguments to explain the isolation of brown lemming populations on Wrangel Isl in the course of their range expansions and contractions within Beringia. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Rodentia - Family Cricetidae, pp. 955-1189 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 2, Baltimore :The Johns Hopkins University Press on page 987, DOI: 10.5281/zenodo.7316535